RETRACTED: Implementasi pendidikan karakter pada anak usia dini di Kelompok Bermain Rabbani - Mira Mayasarokh (Departement of Nonformal Education, Graduate Scholl of Universitas Negeri Yogyakarta, 2019)
Following a rigorous and careful concerns and consideration in the review of the article published in JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat) entitled “Implementasi pendidikan karakter pada anak usia dini di Kelompok Bermain Rabbani” Vol 6, No 1, pp. 88-89, March 2019, DOI: https://doi.org/10.21831/jppm.v6i1.14936This paper has been found to violate the principles of JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat) Publication and has been retracted.The article has contained redundant material and throughout a careful examination, the editor has found that the paper has also been published in Jurnal Pelita PAUD, Vol. 3, No. 2, pp. 167-186, 2019, DOI: https://doi.org/10.33222/pelitapaud.v3i2.547 The document and its content have been removed from JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), and reasonable effort should be made to remove all references to this article.